The relict forests of Northwest Peru and Southwest Ecuador - Weigend, Maximilian (2005)
The forest fragments or relict forests on the Western slopes of the Andes in northwest Peru and in south-west Ecuador are fragile ecosystems, which were largely continuous at some stage in the past. The importance and uniqueness of these forests as «refuges» and stable habitats roots partly in their complex diversity and their high levels of endemicity. These in turn are the outcome of a complex topography and ecology. In this introductory chapter 12 studies are analysed, which were presented at the Taller sobre Bosques Relictos de la Vertiente Occidental Andina del Norte del Perú y Sur del Ecuador in May 2004 at the X CONABOT, Trujillo-Perú. This helps to consolidate and update our knowledge on these over 20 forests fragments in northern Peru and two previously unknown fragments are presented for the first time: Bosque La Oscurana (Cajamarca) and Kañaris (Lambayeque). Some ideas are exposed on the the relationships between the relict forests, how to analyse their dynamics, how to characterize their structure and how their conservation may be achieved. It is proposed that crucial elements in a conservation of these forests are a) urgently inventorizing them to demonstrate their high diversity b) emphasizing their economic potential with respect to the abundance of phytogenetic ressources c) evaluating their role as catchment areas for the rivers which are the primary source of water for agriculture and urban life on the coast.